1993
DOI: 10.1099/0022-1317-74-5-911
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Determination of the P Gene of Simian virus 41: Presence of Irregular Deletions Near the RNA-Editing Sites of Paramyxoviruses

Abstract: The complete nucleotide sequence of the P gene of simian virus 41 (SV41) was determined. The gene was found to be 1406 nucleotides long and to contain a relatively small open reading frame encoding a cysteinerich V protein with a calculated M r of 24 076. We have demonstrated that RNA-editing events occur in SV41 P gene transcripts and that the ratio of edited mRNAs to faithfully copied mRNA (P-mRNA :V-mRNA) is about 1:5 at either 24 or 40 h post-infection. The mRNA with two G insertions was capable of encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The hPIV2 V protein shows 69.3 and 41.1% homology with those of SV41 and PIV5, respectively (26,28). As shown in Fig.…”
Section: Resultsmentioning
confidence: 78%
“…The hPIV2 V protein shows 69.3 and 41.1% homology with those of SV41 and PIV5, respectively (26,28). As shown in Fig.…”
Section: Resultsmentioning
confidence: 78%
“…The P protein of NDV bears limited but distinct similarity to the equivalent proteins from SV5, mumps, hPIV2 and hPIV4A and -4B, as well as the recently reported simian virus 41 sequence (Kawano et al, 1993) (not shown). Of these viruses, all but NDV encode the V protein from an unedited transcript of the P gene, and insert predominantly two G residues to accomplish the switch to the P reading frame.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to those shown in Fig. 5, the coding schemes of rinderpest virus (RPV) (Yamanaka et aL, 1992) and SV41 (Kawano et al, 1993) are shown.…”
Section: Discussionmentioning
confidence: 99%
“…These events occurred in the lineages that lead to: (1) Avian paramyxovirus 11 (APMV-11; genus: Metaavulavirus ), (2) the Rubulaviri nae subfamily, (3) the Ferlaviruses , and (4) Salem virus (SalPV; genus: Salemvirus ). Edit patterns have been experimentally investigated for three of these four clades: 10 members of the Rubulavirinae ( Thomas, Lamb and Paterson 1988 ; Kondo et al 1990 ; Ohgimoto et al 1990 ; Paterson and Lamb 1990 ; Southern, Precious, and Randall 1990 ; Takeuchi et al 1990 ; Kawano et al 1993 ; Bowden et al 2001 ; Chua et al 2001 ; Lau et al 2010 ), 2 Ferlaviruses ( Kurath et al 2004 ; Woo et al 2014 ), and SalPV ( Renshaw et al 2000 ).…”
Section: Evolution Of the Cotranscriptional Gene Editing Systemmentioning
confidence: 99%